Processing Opacity - Hackl, Martin; Koster-Moeller, Jorie; Gottstein, Andrea (Proceedings of Sinn und Bedeutung, 2019)
Objects of intensional transitive verbs (ITVs) can be in interpreted transparently or opaquely. How to represent this ambiguity has been of considerable interest to the field over the years. This paper presents evidence from real time sentence processing to weigh in on that debate. Our evidence supports approaches that rely in an essential way on a syntactic scoping mechanism to explain the ambiguity. Specifically, our evidence suggests that the object of an ITV is interpreted transparently only if it takes syntactic scope over the ITV. If it is inside the syntactic scope of the ITV, it is necessarily interpreted opaquely. Purely semantic approaches to the ambiguity cannot explain this strict dependency between syntactic scope and interpretation.